영유아 기본생활습관 부모 평정척도 개발 연구 - 김명순(Myoung Soon Kim); 변혜원(Hye Weon Byun); 김길숙(Gil Sook Kim) (Korean Journal of child studies, 2011)
The purpose of this study was to develop a basic life habit scale for infant early childhood. The participants of this study were composed of 1,000 parents of children aged from two to five years old in the Seoul, Gyeong-gi, and In-cheon areas. For the purposes of data analysis, the study made use of the following methods : descriptive statistics for SES variables, item-analysis, factor analysis for validity, and Cronbach's a for reliability. Most items were acceptable in terms of item response rates, and item discrimination. The results of factor analysis uncovered six factors, and 46 items were selected from a total of 69 items in the original scale. The six factors were (1) safety and rules (2) neatness (3) manners (4) self-help (5) eating habits (6) cleanliness. Cronbach's a value for the reliability of the factors ranged from .76 to .94.of Cooperative Learning. Methods. Westport, CT : Greenwood Press.